ANALISIS PROFITABILITAS USAHATANI PADI ORGANIK DI PAGUYUBAN AL-BAROKAH KECAMATAN SUSUKAN KABUPATEN SEMARANG - T. Novitaningsih; S. i. Santoso; A. Setiadi (MEDIAGRO, 2018)
The aims of this research are to find out the ammount of profit, profitability, R/C Ratio, and analyzing the ammount of production during 5 years of organic rice farming in the Al-Barokah community, Susukan District, Semarang Regency. This study was conducted on December 2016 – January 2017 in Ketapang Village, Susukan, Semarang. The study method used to collect the data was survey method. The data collected of study was the primary data and the secondary data. The location in this research is selected by several considerations, such as Al-Barokah association is one of farming trade association that uses organic farming system. The populations retrieval used purposive method, then determine the number of samples used the slovin formula. The respondent in this research are 81  farmers  of organic rice. The data analyzed of study was the farming income, R/C Ratio, profitability and trand analysis. Based on the result of income analysis, R/C Ratio and profitability has done that organic rice farming is very feasible and very profitable.Keywords: profitability analysis, farming, organic rice.